New Valid Inequalities for a Multi-Echelon Multi-Item Lot-Sizing Problem with Returns and Lost Sales - Quezada-Valenzuela, F (Springer Science and Business Media Deutschland GmbH, 2021)
This work studies a multi-echelon multi-item lot-sizing problem with remanufacturing and lost sales. The problem is formulated as a mixed-integer linear program. A new family of valid inequalities taking advantage of the problem structure is introduced and used in a customized branch-and-cut algorithm. The provided numerical results show that the proposed algorithm outperforms both the generic branch-and-cut algorithm embedded in a standard-alone mathematical solver and a previously published customized branch-and-cut algorithm. © 2021, Springer Nature Switzerland AG.